2020
DOI: 10.12804/revistas.urosario.edu.co/revsalud/a.8775
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas del PERMA-Profiler para la medición del bienestar en una muestra de estudiantes universitarios chilenos

Abstract: Introducción: en términos científicos y sociales, los estudios sobre el bienestar han sido relevantes en los últimos años, lo que hace necesario investigar acerca de las propiedades psicométricas de los cuestionarios que se utilizan para su medición. El objetivo de este trabajo fue estimar las propiedades psicométricas del cuestionario PERMA-Profiler en una muestra de estudiantes universitarios chilenos. Materiales y métodos: se evaluaron las respuestas de 1462 estudiantes universitarios de una universidad tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
(39 reference statements)
1
7
1
1
Order By: Relevance
“…In other validation studies, Cobo-Rendón et al [42] found a good adjustment of the PERMA model in a sample of Chilean students, although Cronbach's alpha of the Engagement dimension was lower (α = 0.36) when compared to our results (α = 0.46). Watanabe et al [43], in a validation study with a sample of Japanese workers, verified that both the unifactorial and the five-factor models, showed a poor adjustment, although the latter with the best fit.…”
Section: Perma Profiler Model Validation With Structural Equation Modelscontrasting
confidence: 86%
See 1 more Smart Citation
“…In other validation studies, Cobo-Rendón et al [42] found a good adjustment of the PERMA model in a sample of Chilean students, although Cronbach's alpha of the Engagement dimension was lower (α = 0.36) when compared to our results (α = 0.46). Watanabe et al [43], in a validation study with a sample of Japanese workers, verified that both the unifactorial and the five-factor models, showed a poor adjustment, although the latter with the best fit.…”
Section: Perma Profiler Model Validation With Structural Equation Modelscontrasting
confidence: 86%
“…In fact, the results revealed significant and moderate correlations (0.25 ≤ |R S | ≤ 0.5) between the scale of satisfaction with life and the dimensions of the PERMA model. These results may be due to the fact that well-being is a multifaceted construct that can be measured through a series of subjective and objective constructs [41], allowing an individual to subjectively believe that life is desirable, pleasant, and good [42].…”
Section: Perma Profiler Model Validation With Structural Equation Modelsmentioning
confidence: 99%
“…Each domain has three items, with the total score from these domains constituting a measure of well-being. The PERMA profiler also assesses perceived physical health (three items), negative emotion (three items, excluded from the study) and loneliness (one item; Cobo-Rendón et al, 2020). Each question offers a scale of seven points from 0 to 6, as indicated in each item to be consistent with the rest of the questionnaires in the package (see Dawes, 2008).…”
Section: Well-being Perceived Physical Health and Lonelinessmentioning
confidence: 99%
“…Furthermore, Cobo-Rendón et al [ 36 ], found that among 1462 Chilean students with ages averaging 19, their PERMA values were certainly low, with an overall mean of M = 4.95 SD (1.4). While this may be surprising at first, it is consistent with many other studies related to age range and the happiness curve, mainly eudaimonic, which requires a certain maturity.…”
Section: Discussionmentioning
confidence: 99%